Lubuski sektor pozarządowy podstawą budowy lokalnego społeczeństwa obywatelskiego = Lubuskie non-governmental sector as a foundation for creating a local civic society - Łoś-Tomiak, Anna; Wyrwa, Joanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents a description of the non-governmental sector in the Lubuskie region. In the thesis there is made an appraisal of the efficiency and effectiveness of acting in the perspective of participation in structures, forms and areas of action. Moreover, the article presents and analyses ways of financing programs and initiatives as well as the profile of expenses. The article also underlines the essential meaning of non-governmental institutions social employment, which is contributing to the construction and local development of a civic society.
Keywords: województwo lubuskie; społeczeństwo obywatelskie; organizacje pozarządowe